ANALISIS PENGGUNAAN APLIKASI MOBILE BANKING BRIMOBILE - Elni Cahyani Siregar, (2023)
Mobile banking applications have become a popular solution for banking transactions in the digital era. Bank Rakyat Indonesia (BRI) developed the BRI Mobile mobile banking application to meet customer needs. However, an analysis of the use of this application is necessary to understand the level of customer satisfaction and the effectiveness of this application. This writing aims to analyze the use of the BRI Mobile mobile banking application and evaluate the level of customer satisfaction and the effectiveness of this application in meeting user needs. This study uses a survey method with data collection. from BRI Mobile mobile banking application users. Questions in the survey cover aspects of application use, customer satisfaction, and suggestions for improvement. The data were then analyzed statistically. The results of the analysis showed a high level of customer satisfaction with the BRI Mobile mobile banking application. users find this application easy to use, safe, and meet the needs of banking transactions. However, some areas need improvement, such as the interface and application responsiveness. In conclusion, the mobile banking application BRI Mobile makes a significant contribution in facilitating banking transactions for BRI customers, however it needs improvement to enhance the user experience. Keywords: analysis, users, mobile banking applications, BRI Mobile, customer satisfaction.